2013
DOI: 10.3233/jad-2012-121324
|View full text |Cite
|
Sign up to set email alerts
|

β-Alanyl-L-Histidine Rescues Cognitive Deficits Caused by Feeding a High Fat Diet in a Transgenic Mouse Model of Alzheimer's Disease

Abstract: Abstract. Our goal in this study was to determine whether or not feeding young (4 months old) Alzheimer's disease model transgenic mice with a high fat diet (HFD), consisting of 32% fat, is capable of causing cognitive decline and whether treatment with ␤-alanyl-L-histidine (carnosine) is capable of reducing these effects. Carnosine is an endogenous antioxidant and antiglycating agent that is abundantly present in the brain and muscle tissues of vertebrates. After 8 weeks of feeding with HFD, we observed a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
93
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 35 publications
8
93
0
3
Order By: Relevance
“…Microglia are the brain-resident “immune” cells and are proposed to play a key role in many neurodegenerative conditions and particularly in AD (Wyss-Coray and Rogers, 2012). Microglial activation was increased in response to a high-fat diet seen here in both 3xTgAD and non-Tg control mice, and also in other mouse models of AD (Herculano et al., 2013). Vascular inflammation might also be important in the effects of obesity on cognition as diets high in fat also increase expression of vascular inflammatory markers in AD mice (Herculano et al., 2013).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Microglia are the brain-resident “immune” cells and are proposed to play a key role in many neurodegenerative conditions and particularly in AD (Wyss-Coray and Rogers, 2012). Microglial activation was increased in response to a high-fat diet seen here in both 3xTgAD and non-Tg control mice, and also in other mouse models of AD (Herculano et al., 2013). Vascular inflammation might also be important in the effects of obesity on cognition as diets high in fat also increase expression of vascular inflammatory markers in AD mice (Herculano et al., 2013).…”
Section: Discussionsupporting
confidence: 73%
“…Microglial activation was increased in response to a high-fat diet seen here in both 3xTgAD and non-Tg control mice, and also in other mouse models of AD (Herculano et al., 2013). Vascular inflammation might also be important in the effects of obesity on cognition as diets high in fat also increase expression of vascular inflammatory markers in AD mice (Herculano et al., 2013). Furthermore, when AD transgenic mice (APP23) are crossed with an obese mouse model ( ob/ob ) the resulting offspring (APP + - ob/ob ) show worse cognitive deficits and vascular inflammation that appear before significant Aβ deposition (Takeda et al., 2010).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Nevertheless it is possible that a common molecular entity exists whose activities link aging, telomeres, cortisol and behaviour. It is suggested here that carnosine could provide a therapeutic link between these phenomena because, as noted above, carnosine (i) can act as an anti-aging agent (mimicking rapamycin) including exerting beneficial effects on animal models of age-related brain dysfunction [23][24][25][26][27][28], (ii) can help to maintain telomere length [12], (iii) may enhance cortisol metabolism, at least in mice [36], (iv) ameliorates stress-induced changes in metabolism in restrained mice [37] and (v), when complexed with zinc, suppress the effects of cortisol on rat bone metabolism [38]. Interestingly, it has been suggested that carnosine's anti-stress effects in mice are mediated by modulating the stress-activated hypothalamic-pituitary-adrenal axis [37], whilst it has recently been shown that raised cortisol levels are present in Alzheimer's disease patients' cerebrospinal fluid, possibly arising from dysregulation of the hypothalamic-pituitary-adrenal axis [39].…”
Section: Depression Cortisol Aging and Carnosinementioning
confidence: 91%
“…Carnosine can inhibit many deleterious biochemical phenomena thought to be associated with generation of the aged phenotype, these include protein damage (including cross-linking [13]) induced by reactive oxygen species [14], reactive nitrogen species [15,16], reducing sugars [13] and reactive carbonyl species such as malondialdehyde [17], 4-hydroxynonenal [18,19] and methylglyoxal [20]. Model animal studies show beneficial effects of the dipeptide towards a number of age-related physiological conditions including impaired wound healing [21,22], Alzheimer's disease [23,24], Parkinson's disease [25,26], stroke [27,28], atherosclerosis [29,30], cataracts [31,32] and diabetic kidney disease [33,34]. In fact it has been claimed that carnosine may be a rapamycin mimetic (a well-recognized anti-aging agent) because many of their respective properties are so similar [35], and recent evidence supports this proposal [10].…”
Section: Carnosine and Agingmentioning
confidence: 99%